Learning with and from: positioning school students as advisors in pre-service teacher education. Issue 3 (26th May 2016) - Cahill, Helen; Coffey, Julia; McLean Davies, Larissa; Kriewaldt, Jeana; Freeman, Elizabeth; Acquaro, Daniela; Gowing, Annie; Duggan, Shane; Archdall, Vivienne
Abstract : This article reports on an innovative pedagogical approach within the Learning Partnerships program in which school students help to 'teach the teachers' within pre-service teacher education. Classes of school students join with classes of pre-service teachers to provide input on how teachers can enhance school students' engagement and wellbeing. The article draws on data collected from 125 students (aged 13–16) and 120 pre-service teachers in these workshops. Findings generated from a mixed methods study combining pre-workshop focus groups ( n  = Students: 38, Teachers: 33) and post-workshop focus groups ( n  = Students: 69, Teachers: 15) and post-workshop surveys ( n  = Students: 96; Teachers: 101) demonstrated that the workshops were mutually beneficial for both students and pre-service teachers. Participants found that workshopping together enhanced their belief in the possibility of positive student–teacher relationships. The pre-service teachers reported greater confidence in communicating with young people about the issues that affect student engagement and wellbeing. The school students reported that they were more willing to use teachers as a source of help. Implications include the need for increased attention to a 'third space' for learning in teacher development which provides opportunity for learning with and from young people about how to foster their engagement and wellbeing.